Translating the Cochrane EMBASE RCT filter from the Ovid interface to Embase.com: a case study. (22nd July 2019) - Glanville, Julie; Foxlee, Ruth; Wisniewski, Susi; Noel‐Storr, Anna; Edwards, Mary; Dooley, Gordon
Abstract: Background: Information specialists frequently translate search filters from one interface to another. Publications advise that translation can be complex and should be undertaken carefully. Objectives: To investigate the issues arising when translating the Cochrane Embase RCT search filter from one interface (Ovid) to another (Embase.com ). Methods: We drafted a translation of the Cochrane Ovid RCT filter to run in Embase.com . We compared the line‐by‐line results of the Ovid filter with the results of the translation. We revised the filter. We identified differences between database versions including records with different publication years and subject headings. Some records were in Embase in one interface but not in the other. We encountered expected interface differences relating to proximity operators. We also encountered unexpected interface issues around truncation and the use of the original title or original abstract field. Discussion: Filter conversion is challenging and time consuming revealing unexpected differences in interfaces and databases. Careful planning can pre‐empt some issues, but others may only emerge during testing. We identified interface anomalies that have led database publishers to review aspects of the way their interfaces work. Conclusions: Translators should be vigilant for known and unknown differences in both interfaces and database versions.